Effect on the addition of Pleurotus sajor-caju (PSC) on physical and sensorial properties of beef patty - Wan Rosli, W. I.; Solihah, M.A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Mushrooms are well known to be healthy because they are low in calories, fat and cholesterol level but rich in vitamin and other essential nutrients. The grey oyster mushroom, Pleurotus sajor-caju (PSC), is a common edible mushroom and is now grown commercially around the world for food and food products. The ability of PSC in changing physical characteristics and sensory properties of beef patty formulated with this fungus were investigated. Result shows beef patty added with 50% ground PSC recorded the highest concentration total dietary fibre (TDF) at 9.95 g/100g compared to beef patty containing 25% of PSC (7.00 g/100g) and control (3.90g/100g). Beef which was replaced with 25% of PSC, recorded the highest cooking yield (76.62%) and moisture retention (59.80%) respectively. On the other physical traits, beef patty containing 25% PSC recorded fat retention at 89.04% and was not significant (P<0.05) with control patty (88.59%). However, the fat retention was proportionally decreased with the increment of PSC content in patty formulations. There were no differences recorded in all sensory attributes of PSC-based patties perceived by panelists. The addition of PSC at 25% can be recommended for incorporation in beef patties and permit a reduction of the formulation cost without affecting sensory descriptors of the product to which the consumer is familiarized.